Penggunaan Diaroma Ekosistem pada Pembelajaran IPA - Muslikhun, Muslikhun (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Among the forms of problems in the thematic learning activities of the 2013 curriculum are students having difficulty understanding learning materials and the use of media used by teachers are not appropriate with the material being taught, so students are not interested in learning and difficult to understand the concept of the material being taught, so that learning outcomes are obtained did not reach the expected value. So to overcome these problems requires the use of appropriate media in order to improve student learning outcomes. This study aims to determine the acquisition of student learning outcomes by using a diaroma media on the theme of the ecosystem. The method used is in this study is a quasi-experimental study with a non equivalent control group design. The data that has been collected is then analyzed using quantitative analysis techniques. From the results of research on the use of diaroma media shows that the use of diorama media on ecosystem themes in grade 5 Madrasah Ibtidaiyah increases learning interest and can improve student learning outcomes. Thus the diaroma media can be used for ecosystem material.